Pengaruh Intensitas Komunikasi Interpersonal Pelatih Dengan Atlet dan Motivasi Berprestasi Terhadap Performa Atlet - Anisa Dyah Permata, Cindy; Setyabudi, Djoko; Surayya Ulfa, Nurist (Interaksi Online, 2024)
The low performance of athletes causes the achievements obtained are not maximized according to the target. In the shorinji kempo sport in Central Java. Experiencing a decline in achievement since the last few years, this is due to the low performance of athletes. This study aims to determine whether there is an effect of the coach's interpersonal communication intensity with athletes and the athlete's achievement motivation on athlete performance. The research method used is explanatory quantitative. Data collection using an online questionnaire distributed to 60 Central Java shorinji kempo athletes. The theories used in this study are social exchange theory and achievement motivation theory. The results of this study indicate that the hypothesis test of the intensity of the coach's interpersonal communication with athletes on athlete performance produces a sig. value. < 0.05, which is 0.00 < 0.05 and the R square value is 22.2%. Meanwhile, achievement motivation on athlete performance produces a sig value. < 0.05, which is as large as 0.00 < 0.05 and the R square value is 24.7%. So it can be said that there is an influence of the intensity of interpersonal communication between coaches and athletes (X1) on athlete performance (Y), and there is an influence of achievement motivation (X2) on athlete performance (Y). Suggestions from this study, coaches and athletes can further increase the attention given to each other when communicating, then the coach can convey references and input to athletes to increase athlete performance